Influence of Different Light-Dark Cycles on Motility and Photosynthesis of Euglena gracilis in Closed Bioreactors - Richter, Peter R. (Mary Ann Liebert, Inc., 2014)
The unicellular photosynthetic freshwater flagellate Euglena gracilis is a promising candidate as an oxygen producer in biological life-support systems. In this study, the capacity of Euglena gracilis to cope with different light regimes was determined. Cultures of Euglena gracilis in closed bioreactors were exposed to different dark-light cycles (40 W/m(2) light intensity on the surface of the 20 L reactor; cool white fluorescent lamps in combination with a 100 W filament bulb): 1 h–1 h, 2 h–2 h, 4 h–4 h, 6 h–6 h, and 8 h–16 h, respectively. Motility and oxygen development in the reactors were measured constantly. It was found that, during exposure to light-dark cycles of 1 h–1 h, 2 h–2 h, 4 h–4 h, and 6 h–6 h, precision of gravitaxis as well as the number of motile cells increased during the dark phase, while velocity increased in the light phase. Oxygen concentration did not yet reach a plateau phase. During dark-light cycles of 8 h–16 h, fast changes of movement behavior in the cells were detected. The cells showed an initial decrease of graviorientation after onset of light and an increase after the start of the dark period. In the course of the light phase, graviorientation increased, while motility and velocity decreased after some hours of illumination. In all light profiles, Euglena gracilis was able to produce sufficient oxygen in the light phase to maintain the oxygen concentration above zero in the subsequent dark phase. Key Words: Euglena gracilis—Bioreactor—Light-dark cycle—Motility—Gravitaxis. Astrobiology 14, 848–858.